Producing journalism about climate change for news and agricultural radio: a case study of Malawi's public broadcaster - Kapiri, Francis (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
This study investigates how radio journalists at the Malawian public broadcaster (MBC) experience the task of producing content that can help their audiences to engage with the local relevance of climate change. This study establishes terms of reference for this research by mapping out international histories of public engagement with the concept of climate change in the domains of science, politics and the media. It describes how contestations around climate change have evolved within these spheres and concludes that such contestation is shaped by relations of power that inform the international economic domain. The study then examines scholarly evaluations of journalism about climate change, concluding that such evaluation is grounded in distinct normative understandings of the social purpose of such journalism. It is argued that research about Malawian journalists' experience of reporting on climate change should draw on knowledge of the role that norms play within this local environment. With this goal in mind, the study reviews tools for the analysis of the normative foundations of journalism within specific socio-historic contexts. It demonstrates the relevance of these tools for the identification of norms and their influence on journalism about climate change in the Malawian context. The empirical component of the study draws on this framework by means of a case study of the experiences of journalists working at the MBC. It examines how these journalists experience the task of producing content that enables their audiences to engage with the local relevance of climate change. It compares such experience as articulated by journalists working for agricultural and news programming. It is concluded that the participants have access to credible knowledge about climate change and its relevance to the Malawian context. Based on such knowledge, they articulate a shared understanding of climate change and its relevance to the Malawian context. However, the study identifies differences in the way that the two groups make sense of the practice of producing journalism about climate change that is of relevance to their audience. In particular, the agricultural journalists incorporate a more inclusive and diverse set of norms into their conceptualisation of such practice. At the same time, the two groups nevertheless respond similarly when commenting on institutional factors at MBC that constrain or enable them to produce journalism about climate change that is guided by such norms. They place emphasis on the need for MBC to provide opportunities for journalists to have access to training, facilitated by organisations that have expertise in climate change journalism. It is concluded that the participants recognise that, despite the entrenched culture of authoritarianism at MBC, such workshops can contribute fundamentally to the shaping of journalistic practice within this broadcaster.
Keywords: Public radio -- Malawi; Climatic changes in mass media; Climatic changes in mass media -- Case studies -- Malawi; Radio in agriculture -- Malawi; Malawi Broadcasting Corporation